Central-node Based Clone Detection in Mobile Wireless Sensor Networks - raj, Dr.J.Anthoniraj (INFOCOMP Journal of Computer Science, 2021)
Clone Attack is the very dangerous attack of all the active attacks of Wireless Sensor Network. In this attack, the adversary capture a sensor node from the network with help of that adversary can create any number clone nodes. Clone nodes are controlled by the adversary, which has all the secret keys. So that clone attack is most harmful threat which is very difficult to detect. In mobile sensor network, the nodes move from one location to another regularly. So it is a complicated task to find the clone nodes which exist in the mobile sensor networks. The proposed Central-node Based Clone Detection(CBCD) protocol detect the clone nodes in efficient manner and within minimum detection time compared with existing EDD and XED protocols. The advantage of proposed CBCD protocol include 1) High clone detection ratio; 2) Minimum communication overhead; 3) Minimum End-to-End delay; 4) Minimum latency time; 5) High throughput so on.